Management and outcome of sight-threatening diabetic retinopathy in pregnancy - Chan, W. C.; Lim, Lik Thai; Quinn, M. J.; Knox, F. A.; McCance, D.; Best, R. M. (Nature Publishing Group, 2004)
Aims To report the management and outcomes of sight-threatening diabetic retinopathy in pregnancy. Methods A retrospective review of 8 diabetic females who developed pregnancy related sight-threatening diabetic retinopathy requiring treatment over a 12-year period. Results In total, 16 eyes of eight patients were included in this series. The mean age of the patients at presentation was 30.75 years 73.8SD and the mean duration of diabetes was 21.0 years 75.1 SD. The mean follow-up period was 46.75 months 747.2 SD. A total of 87.5% of patients showed progression of diabetic retinopathy during pregnancy, 71% of which were in the sight-threatening proliferative category. In the postpartum period, 81% of patients continued to progress to proliferative diabetic retinopathy, requiring panretinal photocoagulation and multiple other surgical procedures. In all, 69% of eyes retained visual acuity equal to or better than 0.3 logMAR units (6/12).